HUBUNGAN LAMA MENJALANI TERAPI HEMODIALISIS DENGAN KUALITAS HIDUP PADA PASIEN GAGAL GINJAL KRONIK YANG MENJALANI HEMODIALISIS DI RUMAH SAKIT GINJAL RASYIDA MEDAN - Elida Sinuraya; Lismayanur Lismayanur (UNIVERSITAS SARI MUTIARA INDONESIA, 2019)
Chronic Renal Failure (CRF) is a worldwide health problem. One of the renal replacement therapies is hemodialysis. This therapy is an action used on the client's CRF to remove toxic substances, excess fluid to improve electrolyte imbalance. Haemodialiysis therapy have positive and negative effect. However, in addition there are positive effects of hemodialysis therapy that is lived and the negative effects that can affect the quality of life of patients. The aim of this study is to examine the lenght of haemodialysis therapy and quality of life in chronic renal failure patients on hemodialysis therapy, and their relationship. The participant were 75 patient, the data were collected in march 2018 using whoqol-BREFF questionnaire which explored the quality of life and the data from medical record was taken to explored the lenght of haemodialysis therapy. Then the data was analyzed using pearson produc't moment. Result, the lenght of haemodialysis therapy was <12 months (52%) and quality of life in chronic renal failure patients on hemodialysis therapy was poor (67,%). There is no statistically relationship between lenght of haemodialysis therapy and quality of life in chronic renal failure patients with p value = 0.115 (> 0.05). Conclusion, the quality of life of patients on hemodialysis patiens due to chronic renal failure has no correlation with the lenght of haemodialysis therapy. Suggestion, need to explore the factors related to quality of life in chronic renal failure patients on hemodialysis therapy.